Tela'ah Interpretasi QS. Lukman: 33 Dalam Membangun Konsistensi Kesadaran Akuntabilitas diri Secara Kaffah - Hanian Marian; Komarudin Sassi (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the interpretation of QS. Luqman: 33 in constructing self-accountability awareness through a thematic interpretation approach and character education perspective. This research aims to analyze the concept of moral responsibility in the Qur’an and its relevance to contemporary social problems such as nepotism, integrity crisis, and weak professionalism. The study employs a qualitative library research method using thematic interpretation (tafsir maudhu’i) combined with the adabi ijtima’i approach. Data were obtained from classical and contemporary tafsir literature, academic journals, and character education studies. The findings reveal three main principles of self-accountability in QS. Luqman: 33: (1) individual moral responsibility, (2) awareness of worldly deception, and (3) transcendental accountability before Allah. Furthermore, the study finds that these values are relevant in strengthening integrity, professionalism, and moral responsibility in the digital era. The study concludes that QS. Luqman: 33 provides a theological foundation for developing Qur’anic-based character education.